2021
DOI: 10.1039/d1py01058a
|View full text |Cite
|
Sign up to set email alerts
|

Multipath oxygen-mediated PET-RAFT polymerization by a conjugated organic polymer photocatalyst under red LED irradiation

Abstract: In this contribution, we propose a novel multipath aerobic-mediated reductive quenching pathway (O-RQP) for PET-RAFT polymerization process, where in situ production of superoxide anion radical from molecular oxygen was achieved...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 54 publications
0
14
0
Order By: Relevance
“…With the options of PCs, PET-RAFT polymerization can be performed using far-red to blue light. [27][28][29][30][31] At these wavelengths, light energy is much lower than that of traditional UV light, which would help reduce safety risks. Additionally, since PET-RAFT polymerization is a light-regulated polymerization process, it has the advantage of being easily turned 'on' and 'off'.…”
Section: Visible Light Polymerizationmentioning
confidence: 99%
See 1 more Smart Citation
“…With the options of PCs, PET-RAFT polymerization can be performed using far-red to blue light. [27][28][29][30][31] At these wavelengths, light energy is much lower than that of traditional UV light, which would help reduce safety risks. Additionally, since PET-RAFT polymerization is a light-regulated polymerization process, it has the advantage of being easily turned 'on' and 'off'.…”
Section: Visible Light Polymerizationmentioning
confidence: 99%
“…One advantage of PET‐RAFT polymerization is that visible light can be used as the irradiation source. With the options of PCs, PET‐RAFT polymerization can be performed using far‐red to blue light 27–31 . At these wavelengths, light energy is much lower than that of traditional UV light, which would help reduce safety risks.…”
Section: Pet‐raft Polymerizationmentioning
confidence: 99%
“…Covalent organic frameworks (COFs) are a category of molecular skeletons with diverse structures that enable precise modulation at the molecular or atomic level to optimize their photocatalytic performance. , Previous studies have shown that COF-mediated photopolymerization is also compatible with the TEA/ 1 O 2 system or the superoxide anion (O 2 •– ) system and confers recyclability. Notably, the aforementioned TEA/ 1 O 2 and O 2 •– systems allow RAFT to achieve high-quality polymerization at low oxygen levels (the oxygen content required for catalysis) .…”
Section: Introductionmentioning
confidence: 99%
“…•− ) system 29 − systems allow RAFT to achieve high-quality polymerization at low oxygen levels (the oxygen content required for catalysis). 24 In most cases, previous work has been focused only on studies in the organic phase (Figure 1a).…”
Section: ■ Introductionmentioning
confidence: 99%
“…Because they can easily be separated and reused, heterogeneous catalysts play an important role in various polymerizations, and increasing attention has been paid to this field in recent years. [30][31][32][33][34][35][36][37][38][39][40][41] However, the use of heterogeneous catalysis in LCP is very limited. Few studies of heterogeneous catalysis of LCP have been reported to date.…”
Section: Introductionmentioning
confidence: 99%